Evaluation of Microdissection Testicular Sperm Extraction Results in Patients with Non-Obstructive Azoospermia: Independent Predictive Factors and Best Cutoff Values for Sperm Retrieval - Cetinkaya, Mehmet; Onem, Kadir; Zorba, Orhan Unal; Ozkara, Hamdi; Alici, Bulent (Urology Journal, 2015)
Purpose: Testicular sperm extraction (TESE) for intracytoplasmic sperm injection (ICSI) was first introduced for the treatment of non-obstructive azoospermia. This study was conducted to detect predictive factors affecting the success of microTESE. Materials and Methods: We retrospectively evaluated the results of 191 cases who underwent microTESE. For each patient, the testicular volume, endocrine profile [follicle stimulating hormone (FSH), luteinizing hormone (LH), free testosterone (FT), total testosterone (TT)], serum inhibin B level, karyotype analysis, and Y chromosome microdeletions were recorded, and all data were analyzed to detect any predictors. The receiver operating characteristic curve, two-sample t-test and regression analysis were used for the statistical analysis. Results: The mean age of the patients was 34.4 ± 5.6 years. Sperm retrieval was successful in 104 (54.5%) patients, and there was no sperm in 87 (45.5%). Seven factors including, testicular size, Johnson score, Y chromosome microdeletion, and serum FSH, LH, FT and TT levels were different between the successful and unsuccessful groups. Six patients had Klinefelter syndrome, and ten patients (5.2%) had a Y chromosome microdeletion (5 AZF-c, 1 AZF-b, 2 AZF-bc, 1 AZF-abc, and 1 AZF-ac). The Johnson score, TT level, family history and Y chromosome microdeletions were determined to be independent predictive factors for sperm found. According to the testicular histology, the sperm-found ratios were 36%, 48.6%, and 95.5% in the sertoli cell only syndrome, maturation arrest, and hypospermatogenesis groups, respectively. Conclusion: According to our results, the Johnson score, TT level, family history-related infertility, and Y chromosome microdeletions were determined to be independent predictive factors for sperm found.